Preserving cultural identity the Japanese judo experience - Gaspar, Rolando R. (2008)
This ethnographic study described how learning martial arts contributes to the preservation of cultural identity among the Japanese. It brought to light how the process of enculturation takes place at the training hall of budo, the collective name for all forms of martial arts.The historical data covered the Samurai Period up to the end of the Feudal Period. Fieldwork was conducted in Tokyo, Japan from June 1997 to December 1998. The study revealed that the school and the community provide opportunities for the inculcation of the cultural values through judo. How the teaching of judo contributes to the preservation of Japanese cultural identity once again proves that the school serves as an arena for cultural transmission. The Filipino proponents of arnis can learn from the Japanese how an indigenous sport can continue to gain national patronage and international acceptance.